If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = (2y) + 15 Reorder the terms: y = 15 + (2y) Solving y = 15 + (2y) Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '(-2y)' to each side of the equation. y + (-2y) = 15 + (2y) + (-2y) Combine like terms: y + (-2y) = -1y -1y = 15 + (2y) + (-2y) Combine like terms: (2y) + (-2y) = 0 -1y = 15 + 0 -1y = 15 Divide each side by '-1'. y = -15 Simplifying y = -15
| 7x+21x-8=7(4x+9) | | (y^2+4y+4)(y+2)= | | 2x^3=129 | | 8m-7=5m+11 | | z(t)=120(1/2)^t/32760 | | -16t^2-h+245=0 | | 6=1-3z | | 4x+x^2-25=2304 | | 19x-3=21X-5 | | 5x+19x-7=6(4x+3) | | 14x-118=62+5x | | h=-16t^2-11t+120 | | 2x-187=72-5x | | 2x-(x-1)=5(x-3) | | 42x^2-5x-3=0 | | -20=2(w+7)-4w | | t/25=14/10 | | -9x-73=67-14x | | 4x+26x-9=6(5x+5) | | 3x-6=40 | | 3x-6+2x-4=30 | | 5x-40=8x+11 | | 28-4x=13-9x | | -161+8x=2x+99 | | 12x+15=5x+7 | | (x-1)+(x-1)=g | | y-2=(22-y)^(1/2) | | -114-2x=210+7x | | (x^2)-2x-2.5=0 | | 3a-27=54+9a | | 3x-22=13+4x | | -14+10x=11x+13 |